Escalating the conflict? Intersex genetic correlations influence adaptation to environmental change in facultatively migratory populations. (30th March 2022) - Kane, Adam; Ayllón, Daniel; O'Sullivan, Ronan James; McGinnity, Philip; Reed, Thomas Eric
Abstract: Males and females are often subject to different and even opposing selection pressures. When a given trait has a shared genetic basis between the sexes, sexual conflict (antagonism) can arise. This can result in significant individual‐level fitness consequences that might also affect population performance, whilst anthropogenic environmental change can further exacerbate maladaptation in one or both sexes driven by sexual antagonism. Here, we develop a genetically explicit eco‐evolutionary model using an agent‐based framework to explore how a population of a facultatively migratory fish species (brown trout Salmo trutta ) adapts to environmental change across a range of intersex genetic correlations for migration propensity, which influence the magnitude of sexual conflict. Our modelled focal trait represents a condition threshold governing whether individuals adopt a resident or anadromous (sea migration) tactic. Anadromy affords potential size‐mediated reproductive advantages to both males and females due to improved feeding opportunities at sea, but these can be undermined by high background marine mortality and survival/growth costs imposed by marine parasites (sea lice). We show that migration tactic frequency for a given set of environmental conditions is strongly influenced by the intersex genetic correlation, such that one sex can be dragged off its optimum more than the other. When this occurred in females in our model, population productivity was substantially reduced, but eco‐evolutionary outcomes were altered by allowing for sneaking behaviour in males. We discuss real‐world implications of our work given that anadromous salmonids are regularly challenged by sea lice infestations, which might act synergistically with other stressors such as climate change or fishing that impact marine performance, driving populations towards residency and potentially reduced resilience.